Assessing the Impact of Interorganizational Linkages on Medical Home Model Adoption by U.S. Acute Care Hospitals. (February 2023) - Hearld, Larry R.; Tafili, Aurora
The medical home model aims to increase care coordination and health care quality. While the adoption of the model has been increasing, the role of U.S. acute care hospitals' interorganizational linkages on adoption is yet to be explored. Using a national sample of hospitals throughout the United States, we examined what interorganizational linkage features are associated with medical home adoption of hospital-owned physician practices and assess the pattern of adoption by acute care hospitals between 2011 and 2019. A generalized estimating equation with binomial distribution was utilized to assess the association between interorganizational linkages and medical home adoption. Hospitals with structural linkages and institutional linkages were more likely to have adopted the medical home. Moreover, the likelihood of medical home adoption increased relative to an increasing number of interorganizational linkages. Medical home adoption and dissemination efforts may be more effective when focused on hospitals possessing interorganizational linkages, specifically those with structural linkages.